'Vulnerable Refugees' and 'Voluntary Deportations': Performing the Hotspot, Embodying Its Violence. Issue 4 (8th August 2022) - Spathopoulou, Aila; Carastathis, Anna; Tsilimpounidi, Myrto
ABSTRACT: In this paper, we intervene in naturalised distinctions based on problematic assumptions about agency and choice that underpin the global regime of migration management: namely, that categories of human mobility can be ontologically and juridically distinguished from one another in terms of the degrees or forms of freedom they embody, and that different rights legitimately adhere to each. Focussing on the 'hotspots' instituted on 5 islands in the Aegean Sea to manage 'mixed migration flows' during the declared 'refugee crisis, ' we show that the ideological justification for the process of differentiation involves variable attributions of agency, choice, and freedom, or their lack thereof, all of which silence the actual subjects transformed into objects of 'migration management.' We argue that the figure of the refugee is divested of agency through the ascription of vulnerability, while the migrant is invested with economic rationality. However, the forms of vulnerability that internment within the camp produces are excluded by design from vulnerability assessments. By tracing the various paths out of the hotspot – including the IOM's Assisted Voluntary Return and Reintegration Programme – we show that the hotspot is, in essence, a deportation mechanism. This analysis is based on an ethnographic encounter, which illustrates the psychic and physical violence through which the will is bent and shaped, leading some illegalised subjects to 'self-deportation.'